2020
DOI: 10.3389/fimmu.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Human Mesenchymal Stromal Cells Eliminates Their Ability to Suppress Human T Cells

Abstract: Mesenchymal stromal cells (MSCs) are administered locally to treat sites of inflammation. Local delivery is known to cause MSCs to aggregate into "spheroids," which alters gene expression and phenotype. While adherent MSCs are highly efficient in their inhibition of T cells, whether or not this property is altered upon MSC aggregation has not been thoroughly determined. In this study, we discovered that aggregation of MSCs into spheroids causes them to lose their T cell-suppressive abilities. Interestingly, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 54 publications
(73 reference statements)
5
32
0
Order By: Relevance
“…Although there is some evidence that 3D cultivation as spheroids can reduce the anti-inflammatory and immunomodulatory potential of MSCs [ 98 ], most secretomes produced by MSCs cultivated in 3D hydrogels seem to have higher anti-inflammatory and immunomodulatory properties, and an overall greater regenerative potential compared to both spheroids and conventionally cultivated cells.…”
Section: Impact Of 3d Cell Culture On Bone Regeneration-relevant Propmentioning
confidence: 99%
“…Although there is some evidence that 3D cultivation as spheroids can reduce the anti-inflammatory and immunomodulatory potential of MSCs [ 98 ], most secretomes produced by MSCs cultivated in 3D hydrogels seem to have higher anti-inflammatory and immunomodulatory properties, and an overall greater regenerative potential compared to both spheroids and conventionally cultivated cells.…”
Section: Impact Of 3d Cell Culture On Bone Regeneration-relevant Propmentioning
confidence: 99%
“…These findings were confirmed with the use of a CD73 enzyme inhibitor (adenosine 5′‐(α, β‐methylene) diphosphate [APCP]), which decreased the Ado production and led to a statistically significant reduction in MSC migration capability compared to control. Curiously, a recent study also demonstrated that the aggregation of MSCs into spheroids causes a significant reduction in the expression and activity of the CD73 enzyme compared to adherent MSCs 115 . Indeed, this role of the CD73 enzyme as an adhesion molecule and consequently involved in cell migration was already suggested for other cell types 39,116 .…”
Section: Adenosinergic Signaling In Proliferation Migration and Homing Of Mscsmentioning
confidence: 94%
“…Indeed, the use of P1 receptor inhibitors, such as caffeine (nonselective), ZM241385, or SCH58261 (A2 A R antagonist) restored the T‐lymphocyte proliferation 21,143,193,194 . However, Burand et al 115 recently showed that the in vitro cell culture method can influence the MSC's immunosuppressive role. In this study, they observed that human MSCs aggregated into spheroids lose the ability to suppress activated T cell proliferation due to reduced expression and activity of the CD73 enzyme 115 …”
Section: Adenosinergic Signaling In Immunomodulatory Effects Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the immunomodulatory effect of multipotent MSC, either preconditioned with inflammatory cytokines or apoptotic, metabolically inactivated or even fragmented cells, is transmitted via a variety of secreted cytokines or factors, and surface molecules ( Table 1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. As a consequence, MSC have the ability to interact and change the functional properties of diverse host immune cells, either from the innate or the adaptive immune system ( Table 2 ) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Immunomodulatory Effects Of Mesenchymal Stem Cellsmentioning
confidence: 99%